Effect of Foot Exercise and Sago-Based Dietary Education on Fasting Blood Glucose Among Patients with Diabetes: A Quasi-Experimental Study in Ambon, Indonesia - Syulce Luselya Tubalawony; Mevi Lilipory; Vernando Yanry Lameky (Media Publikasi Cendekia Indonesia, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disorder and a major global health challenge, with its prevalence continuing to rise in both developed and developing countries. This increase contributes to high morbidity and mortality rates, underscoring the importance of effective and sustainable management strategies. Conventional DM management typically includes health education, regular physical activity, dietary modification, pharmacological therapy, and routine blood glucose monitoring. In addition, non-pharmacological interventions that utilize local resources and cultural practices are gaining attention for their role in supporting glycemic control and improving patients’ quality of life. This study aimed to analyze the effectiveness of foot exercise and sago-based dietary education on blood glucose levels among diabetic patients at Belakang Soya and Waai Health Centers, Ambon. A quasi-experimental design was employed involving 152 respondents (93 intervention, 59 control) selected through purposive sampling. The intervention was conducted over seven days, and blood glucose levels were measured using a GlucoDr glucometer. The Wilcoxon test showed a significant difference in fasting blood glucose levels (p<0.001) before and after the intervention, while the Mann-Whitney test indicated a significant difference in fasting blood glucose levels (p<0.001) between the intervention and control groups. These findings suggest that integrating foot exercise with sago-based dietary education may serve as an effective complementary strategy in DM management. By combining simple physical activity with culturally relevant dietary practices, this approach has the potential for broader application in community health programs. Further research is needed to assess its long-term effects, scalability, and cultural adaptability in community-based diabetes care.